Peran Guru Bimbingan dan Konseling dalam Membentuk Karakter Islami Siswa di Madrasah Aliyah Muhammadiyah Sengkang Kecamatan Tempe Kabupaten Wajo - Jumari Jumari; Amirah Mawardi; Ratna wulandari (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to describe the role of Guidance and Counseling (GC) teachers in shaping students’ Islamic character at Madrasah Aliyah Muhammadiyah Sengkang, Tempe District, Wajo Regency. The study employed a descriptive qualitative approach using observation, in-depth interviews, and documentation techniques. Research subjects included GC teachers, homeroom teachers, the principal, and students. The total student population was 129, with observational findings indicating that 24 students still demonstrated low Islamic character, reflected in weak responsibility, social awareness, and behavioral discipline. The results show that GC teachers play strategic roles as counselors, motivators, facilitators, role models, and evaluators through individual counseling services, personal–social guidance, and religious habituation programs such as dhuha prayer, short sermons, and Qur’anic recitation. Individual counseling services produced observable behavioral improvements, including increased worship discipline, honesty, responsibility, and social care. The findings confirm that Islamic character development is most effective through integrated counseling services, role modeling, habituation practices, and teacher collaboration. This study strengthens the position of school counseling services as a key instrument in Islamic character formation within madrasah education.